PERLINDUNGAN HUKUM TERHADAP PEKERJA PEREMPUAN YANG BEKERJA PADA MALAM HARI DITINJAU BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Tiara Selvia Putri (Universitas 17 Agustus 1945 Samarinda, 2019)
AbstractWomen workers in the industrial and economic sectors who are vulnerable will get unfair protection for workers. Imbalance gender terms of remuneration such as family allowances that are only given to men is clearly seen versus women. Women with biological interests who need affirmative action. The problem in this study is the problem of protection for women workers who work at night and how the consequences for companies that do not provide legal protection for women workers who work at night between 23:00 to 07:00. Protection of female workers who work at night has a legal basis under the umbrella of Law No. 13 of 2003 concerning Employment. The method used in this study uses normative juridical research methods. Based on the results of the study, Protection of women workers who work at night has a legal basis under the umbrella of Law No. 13 of 2003 concerning Labor. Women workers who work at night are provided in the form of working hours protection, menstrual protection, pregnancy & childbirth protection, breastfeeding protection and salary protection. The consequences for companies that do not provide protection for women workers who work at night are regulated in Article 187 of Law No. 13 of 2003 concerning employment.